The Itawes family as agent of new evangelization - Ballinan, Joshua Leonard M (Immaculate Conception School of Theology : [s.n.], 2020)
The twenty-first century has produced a new culture and is experienced as increasingly characterized by ethnicity, technology, money, media and new ideologies. The need to hold on to the cultural values of the family by its purification can be a good means for evangelization and for the continuity of the character and values of the Itawes family. The Itawes family is traditionally rooted in its cultural family values, faithful to their traditions, and living the indigenous family values that make every family united wherever they are. The centrality of Itawes family as, among other things, agents of evangelization and catechesis, was the product of the purification of culture taught by the missionaries. This proves that Itawes families are missionary by nature and increase their faith in the act of sharing that faith with others, above all, with their children. The act of living a life of communion as a family is the primary form of proclamation. Thus by this culture and tradition of the Itawes families they can be agents of the New Evangelization in the twenty-first century.
Bibliography: pages 105-110.
CHED-La Union
Keywords: Religious life -- Philippines (Itawes, Cagayan).